काव्यलक्षणम् - Narkanthiravasastri (Shree Somnath Sanskrit University Junagadh Gujarat, 2016)
The book is a commentary book on Kavyalakshanam by Narkanthiravasastri. Kavyalakshanam is a popular word in sanskrit literature
Kavyalakshanam
Keywords: काव्यलक्षणम्; Kavyalakshanam; Literature; Sanskrit